Electrolytic water technology based on transformable and amorphous liquid metal electrodes. Issue 3 (3rd May 2022) - Xu, Shuo; Xing, Zerong; Liu, Jing
Abstract: Hydrogen has important values in industrial manufacture, medical health care, and diverse energy application areas. Among the many possible approaches, convenient and safe hydrogen production from water electrolysis has always been a preferred in situ hydrogen supply technology. So far, many of the electrodes thus involved are based on rigid metals or conductive items which may encounter inconvenience or insufficiency sometimes. To achieve targeted release of hydrogen, appropriate administration of suitable flexible hydrogen evolution electrodes is the key. In recent years, gallium‐based liquid metals have emerged in the field of flexible and biological electrodes. Starting from this point, liquid metal is proposed here as a transformable amorphous electrode for hydrogen evolution in electrolytic water which may help mold new conceptual electrolysis and energy utilization ways. The electrochemical performances and flexible behaviors lying behind are investigated and clarified. According to the experiments, the catalytic activity of the liquid metal itself generally is not remarkable, but it would be significantly improved after being composited with certain active materials such as nickel. Further, the controllability, flexibility, and adaptability of liquid metal‐based amorphous materials which are unmatched by other electrode materials were evaluated. Overall, the motions of such shape transformable liquid metal electrodes could be controlled by electric or magnetic fields, and their deformations are compliantly adaptive to different spaces. This might easily expand the area of hydrogen evolution and lead to multisite in situ hydrogen production. The present study demonstrates the value of liquid metals in flexible energy systems and opens up more application possibilities for electrolytic hydrogen production. Abstract : Gallium‐based liquid metals are proposed as transformable electrodes for hydrogen evolution from water electrolysis, whose motions could be controlled by electric or magnetic fields. The amorphous surface provides abundant active sites, and its location can be adjusted to realize distributed multipoint in situ hydrogen production and to extend hydrogen evolution areas.